2018
DOI: 10.3389/fnana.2017.00130
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal, Visceral and Vestibular Inputs May Improve Cognitive Functions by Acting through the Locus Coeruleus and the Ascending Reticular Activating System: A New Hypothesis

Abstract: It is known that sensory signals sustain the background discharge of the ascending reticular activating system (ARAS) which includes the noradrenergic locus coeruleus (LC) neurons and controls the level of attention and alertness. Moreover, LC neurons influence brain metabolic activity, gene expression and brain inflammatory processes. As a consequence of the sensory control of ARAS/LC, stimulation of a sensory channel may potential influence neuronal activity and trophic state all over the brain, supporting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 258 publications
(322 reference statements)
1
70
0
Order By: Relevance
“…It is also worth considering an alternative, but not necessarily mutually exclusive mechanism through which TMS could exert autonomic influences is through the cranial nerves which are stimulated during the delivery of magnetic pulses. In this case, afferent projections of the trigeminal nerves to the brainstem could also indirectly engage autonomic pathways (Colzato and Vonck, 2017;De Cicco et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth considering an alternative, but not necessarily mutually exclusive mechanism through which TMS could exert autonomic influences is through the cranial nerves which are stimulated during the delivery of magnetic pulses. In this case, afferent projections of the trigeminal nerves to the brainstem could also indirectly engage autonomic pathways (Colzato and Vonck, 2017;De Cicco et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The elaborated, complex, aberrant movements in RBD symptoms resemble as activities in awake status ( 44 ), and patients with RBD symptoms showed abnormalities in sleep-wake transitions ( 11 ), which suggested that RBD symptoms might relate to abnormal “like-arousal” status. Ascending reticular activating system (ARAS), involved in the transition from slow waves to REM sleep ( 45 , 46 ), could be activated through by hippocampus and amygdala ( 15 , 47 ). Therefore, we postulated that increased nodal properties in limbic system might play an over-activation role in regulation of ARAS, which promotes the level of “like-arousal,” leading to the abnormal motor behavior in REM sleep of PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…By 1949, Moruzzi and colleagues demonstrated the importance of trigeminal afferents in maintaining an arousal status, and these afferents were later shown to be essential for proper functioning of the arousal system. Projections from the main spinal and mesencephalic nucleus of the trigeminal to the various noradrenergic nuclei of the encephalic trunk are widespread, and they are responsible for modulation of the arousal state through an ascending reticular activating system and through structures that control the tonic state of the musculature of the head, neck, and ocular motion [61][62][63][64].…”
Section: Discussionmentioning
confidence: 99%